Enhancing IT Service Desk for Hybrid Work: Insight from a TOE and TTF Case Study - Marcel, Marcel; Aotearoa, Garpepi Hanief (Universitas Bina Darma, 2025)
Adopting hybrid work has brought new challenges of IT service desks in small companies with limited resources. This study focuses on a software company in Jakarta with 15 employees, exploring how its size influences the ability to resolve issues, manage tickets, and keep both remote and on-site staff satisfied. Utilizing the Technology-Organization-Environment (TOE) Framework and the Task-Technology Fit (TTF) Model, we investigated ticket records, surveyed 13 employees, and conducted group discussions for deeper analysis. On average, the initial response time was 3.5 hours, but remote staff often faced slower resolutions, averaging 3.8 hours compared to 3.2 hours for on-site employees. The most common problems were connectivity issues, which made up 40 percent of tickets, and login and access challenges, which made up 30 percent. Feedback from a Survey indicated moderate satisfaction with most ratings between 3 and 4 on a 1–5 scale, with gaps in communication and guidance, particularly for remote workers being identified. We suggest refined troubleshooting, enhanced communications, and simplified tracking methods for monitoring issues (real time) to overcome these challenges. These improvements may allow small businesses to make the most of IT support, minimize recurring issues and better accommodate hybrid workplace needs.